Use Of The Dehasen Library Instagram Account In Library Branding Efforts - Fadila, Hafiza Nurul; Darubekti, Nurhayati; Samosir, Fransiska Timoria (IQRA`: Jurnal Perpustakaan dan Informasi, 2024)
Branding is an effort to build a positive identity and image for an institution. This research aims to understand the branding process carried out by the Dehasen Library through its Instagram account @perpustakaan_unived. Using Field Research methods with a qualitative approach, data was collected through three techniques: observation, interviews, and documentation. This study analyzed the digital marketing communication strategy of the library based on the SOSTAC theory. The research results indicate that although branding through Instagram is an essential effort to promote the library, the branding efforts by the Unived Library are not yet optimal. The Dehasen Library has implemented digital branding management steps including situation analysis, objective setting, strategy development, tactic determination, action implementation, and control. However, several indicators have not been properly implemented, such as communication, time-setting, program planning, and training. One of the reasons for this is the lack of attractive Instagram content management and the absence of dedicated human resources (HR) for managing the Instagram account. In summary, despite the Dehasen Library following some of the digital branding management steps according to the SOSTAC model, there are key aspects that need improvement to optimize digital branding. Recommendations for improvement include enhancing  the quality and frequency  of Instagram content, involving suggestions and feedback from followers to create more engaging content, and providing training for the staff responsible for managing social media. With these steps, the library is expected to increase the number of Instagram viewers and strengthen its positive image among students and the academic community.